Mycorrhizas in Agroecosystems - Pagano, Marcela C. (2016)
The increasing consideration for more information to better understand agroecosystems and soils under different management has been recognized. The study of surface and deep soil responses to global change and how to enhance the resilience of soil ecosystems is thus urgently recommended. The examination and use of arbuscular mycorrhiza, which link the biotic and soil components providing ecosystem services for crops in the different associated soils, is reviewed. This chapter discusses advances in mycorrhizal fungi potential drawing on recent research worldwide. Studies on mycorrhizas have developed largely; however, the applications of mycorrhizas in agriculture and environmental issues are still incipient, and its limitations are also discussed.